Unified design approach for systems engineering by integrating model‐based systems design with axiomatic design. Issue 1 (29th August 2019) - Wang, Haoqi; Li, Hao; Tang, Chengtong; Zhang, Xu; Wen, Xiaoyu
Abstract: Model‐Based Systems Design (MBSD) formalizes the application of system modeling. However, it is still difficult for designers to implement MBSD in practice. One of the challenges is to make the field of design more unified, as different MBSD methodologies focus on specific areas, and various designers from different areas use ambiguous terms. Moreover, the failure of some products originates in undiscovered couplings of functions in the design stage. Axiomatic Design (AD) provides a scientific foundation for system design. In order to reduce ambiguity and alleviate functional couplings, this paper integrates AD with the MBSD and proposes a unified systems design approach, called Axiomatic Model‐Based Systems Design (A‐MBSD). A‐MBSD uses four pillars: (a) the fundamental framework of AD; (b) the Independence Axiom; (c) a new behavior domain (BD); and (d) an A‐MBSD modeling profile. Finally, the design of a Forest Fire Satellite Monitoring and Control System demonstrates that the proposed approach can improve unity and alleviate the coupling of functions in a system design.